2014
DOI: 10.1016/j.diii.2014.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Radionecrosis of malignant glioma and cerebral metastasis: A diagnostic challenge in MRI

Abstract: Detecting a new area of contrast-enhancement at MRI after irradiation of malignant brain tumor arises the problem of differential diagnosis between tumor recurrence and radiation necrosis induced by the treatment. The challenge for imaging is to distinguish the two diagnoses given: the prognostic and therapeutic issues. Various criteria have been proposed in the literature based on morphological, functional or metabolic MRI. The purpose of this study was to perform an analysis of these tools to identify MRI be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 68 publications
0
30
1
1
Order By: Relevance
“…In the literature, there are contradictory data. 20 In fact, the apparent diffusion coefficient values were found to be significantly lower in cases of tumor recurrence compared with radionecrosis in some studies; however, in other series, no significant difference was found between the groups. Moreover, in a study by Sundgren, the mean apparent diffusion coefficient values were found to be significantly higher in the recurrence group.…”
Section: Diagnosismentioning
confidence: 87%
“…In the literature, there are contradictory data. 20 In fact, the apparent diffusion coefficient values were found to be significantly lower in cases of tumor recurrence compared with radionecrosis in some studies; however, in other series, no significant difference was found between the groups. Moreover, in a study by Sundgren, the mean apparent diffusion coefficient values were found to be significantly higher in the recurrence group.…”
Section: Diagnosismentioning
confidence: 87%
“…The response assessment in neuro-oncology (RANO) recommends using 2-dimensional measurements (diameter) of contrast enhancement on post-treatment Gadolinium-enhanced T1-weighted (Gd-T 1w ) MRI (with respect to pre-treatment MRI) as the fundamentally quantifiable imaging criteria for assessment of response to treatment. However, due to similar appearance on follow-up post-treatment Gd-T 1w MRI, differentiating RN and tumor recurrence using 2-dimensional measurements of contrast enhancement (as manually identified by an expert) is clinically extremely challenging [5]. Recent studies have displayed promise in utilizing semiquantitative MRI measures such as apparent diffusion coefficient ratios [6], choline, creatine, N-acetyl aspartate ratios from MR spectroscopy [7], and perfusion imaging [8] for differentiating RN from tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Cranial radiation can lead to radiation necrosis in from 3% to 25% of patients, often presenting with seizures. Radiation necrosis is more common between 6 and 18 months postradiation and is more likely to develop with higher, concentrated doses (radiosurgery) and re‐radiation …”
Section: Seizures In Patients Who Have Cancer With Brain Lesionsmentioning
confidence: 99%
“…Radiation necrosis is more common between 6 and 18 months postradiation and is more likely to develop with higher, concentrated doses (radiosurgery) and re-radiation. 21,22 Parenchymal brain metastases are encountered in 10% to 30% of patients with systemic cancer, 23 and, of these, 70% to 80% present with multiple metastases (especially melanoma and lung cancer). In men, the most common primary tumor is lung cancer (particularly non-small-cell lung cancer), whereas, in women, breast cancer (particularly triple negative 24 ) is the main offender.…”
Section: Seizures In Patients Who Have Cancer With Brain Lesionsmentioning
confidence: 99%